Determinants of the Thrombogenic Potential of Multiwalled Carbon Nanotubes - Burke, Andrew (2011)
Multiwalled carbon nanotubes (MWCNTs) are cylindrical tubes of graphitic carbon with unique physical and electrical properties. MWCNTs are being explored for a variety of diagnostic and therapeutic applications. Successful biomedical application of MWCNTs will require compatibility with normal circulatory components, including constituents of the hemostatic cascades. In this manuscript, we compare the thrombotic activity of MWCNTs in vitro and in vivo. We also assess the influence of functionalization of MWCNTs on thrombotic activity. In vitro, MWCNT activate the intrinsic pathway of coagulation as measured by activated partial thromboplastin time (aPTT) assays. Functionalization by amidation or carboxylation enhances this procoagulant activity. Mechanistic studies demonstrate that MWCNTs enhance propagation of the intrinsic pathway via a non-classical mechanism strongly dependent on factor IX. MWCNTs preferentially associate with factor IXa and may provide a platform for its activation. In addition to their effects on the coagulation cascade, MWCNTs activate platelets in vitro, with amidated MWCNTs exhibiting greater platelet activation than carboxylated or pristine MWCNTs. However, contrasting trends are obtained in vivo, where functionalization tends to diminish rather than enhance pro-coagulant activity. Thus, following systemic injection of MWCNTs in mice, pristine MWCNTs decreased platelet counts, increased vWF, and increased D-dimers. In contrast, carboxylated MWCNTS exhibited little procoagulant tendency in vivo, eliciting only a mild and transient decrease in platelets. Amidated MWCNTs elicited no statistically significant change in platelet count. Further, neither carboxylated nor amidated MWCNTs increased vWF or D-dimers in mouse plasma. We conclude that the pro-coagulant tendencies of MWCNTs observed in vitro are not necessarily recapitulated in vivo. Further, functionalization can markedly attenuate the procoagulant activity of MWCNTs in vivo. This work will inform the rational development of biocompatible MWCNTs for systemic delivery.